Nationalizations and effciency - Ernesto Crivelli; Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We develop a theoretical model in which ?rms are either private or state-owned. When ?rms become insolvent, the government can intervene with general measures, like subsidies, or by nationalizing ?rms. The government only intervenes when the bankruptcy of a ?rm entails social costs. In a stylized model, we analyze how government interventions a?ect allocative and productive efficiency. Nationalization of private ?rms in case unpro?table investments were made, leads to increased allocative efficiency despite private ownership. The effort level chosen by the managers working for ?rms is also affected by government intervention with an impact on productive efficiency.
urn:nbn:de:bvb:19-epub-13284-6
Keywords: L33; P31; P51; 330; nationalization; efficiency